In-Vitro Anti-Diabetic Activity and Phytochemical Screening of Ethanolic extract of Calotropis gigantea (Linn) - Yadav, Chandrajeet Kumar; Chaube, Akash; Thapa, Shankar; Palikhey, Anjan; Shrestha, Laxmi; Kandel, Kamal (Journal of Universal College of Medical Sciences, 2023)
INTRODUCTION Diabetes Mellitus (DM) is metabolic disorder characterized by hyperglycaemia due to defect insulin release from pancreas and insulin resistance. The present study was aimed to screen the phytoconstituent present in leaf extract and evaluate α- amylase inhibitory activity of ethanolic extract of Calotropis gigantea leaf. Calotropis gigantea also known as crown ﬂower is rich in phytochemicals like alkaloids, saponins, steroids, ﬂavonoids and glycosides. It is used for asthma, bronchitis and dyspepsia, dried whole plant is a good tonic. MATERIAL AND METHODS About 58.45g coarse powder of Calotropis gigantea leaves was extracted with ethanol using Soxhlet apparatus. Then the phytochemical screening of ethanolic extract was done. Different concentration (0.1mg/ml to 1mg/ml) of ethanolic extracts of leaves, acarbose, sitagliptin and metformin was prepared, and all the concentration were evaluated for α- amylase inhibitory activity through spectrophotometric method. RESULTS Maximum inhibition of α- amylase was shown by acarbose at concentration of 1mg/ml and found to be 78.787 ± 0.00240 % whereas plant extract at concentration of 1mg/ml showed inhibition of α- amylase activity 54.6296 ± 0.00282 %. Percentage inhibition of α-amylase activity by plant extract was found to be dose dependent. CONCLUSION It was concluded that Calotropis gigantea leaves possess some bioactive compounds which were responsible for controlling blood glucose level by inhibiting α-amylase and its identiﬁcation, isolation and characterization may lead to development of newer drugs with lesser side effects.